CO-WORKING SPACE DI PONTIANAK DENGAN PENDEKATAN EKOLOGI - Sitanggang, Shanti Octavia; Purnomo, Yudi; Irwin, Irwin (JMARS: Jurnal Mosaik Arsitektur, 2021)
Currently, there is an increase in workforce that start new independent businesses in the creative economy, either as entrepreneurs or freelancers, this  because number of job is not comparable to the number of the workforce. The increase in workers in the creative economy is in line with the digital transformation in Indonesia. The government also responded well to this by making programs related to the creative economy, especially in the digital field. Pontianak City has the potential for development with an increase in the number of workers in the creative economy every year, but Pontianak City does not yet have space to accommodate workers' activities. Co-working space can accommodate workers in the creative economy so they can work in a productive and creative environment. In addition, the provision of supporting digital services in co-working spaces is expected to support entrepreneurs or freelancers in developing their business into the digital field. The co-working space design process uses an ecological approach. Ecological approach is an approach that is environmentally friendly. The Ecological Approach serves as a tool that are implemented towards designs that take into account the potential for the natural surroundings as well as the interrelationships between buildings, nature and people.